2006
DOI: 10.1007/s10811-006-9107-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of germanium dioxide, an inhibitor of diatom growth, on the microscopic laboratory cultivation stage of the kelp, Laminaria saccharina

Abstract: The kelp, Laminaria saccharina, is an economically and biologically valuable seaweed used in integrated multi-trophic aquaculture. The development of the initial microscopic phase of the life cycle of this species is carried out in the laboratory. A treatment of germanium dioxide (GeO 2 ) can be applied to algal laboratory cultures to inhibit the growth of contaminating diatoms. Previous studies reported inhibitory effects also affecting the macroscopic stage of the life cycle of L. saccharina, the sporophyte,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 7 publications
(5 reference statements)
1
35
0
1
Order By: Relevance
“…Sin embargo, en la gran mayoría de los casos el efecto observado sobre las algas es claramente inhibidor [16][17][18]. El desarrollo de E. intestinalis y Ectocarpus sp.…”
Section: Resultados Y Discusiónunclassified
“…Sin embargo, en la gran mayoría de los casos el efecto observado sobre las algas es claramente inhibidor [16][17][18]. El desarrollo de E. intestinalis y Ectocarpus sp.…”
Section: Resultados Y Discusiónunclassified
“…The absence of diatoms in the culture was verified after adding this solution for two weeks. The GeO 2 concentration employed was based on Shea & Chopin (2007), who recommended the addition of 0.0004 to 0.0022 mg of germanium dioxide per liter of seawater to prevent diatom growth without compromising the development of the microscopic phase of Laminaria saccharina (Linnaeus) J.V. Lamour in culture.…”
Section: Resultsmentioning
confidence: 99%
“…This seems counterintuitive; however, Lewin (1966) showed that GeO 2 , though extremely deleterious for diatoms, had no negative influence on energy metabolism of the cells, and even at 400 mg L -1 GeO 2 , cell respiration did not decrease. Shea and Chopin (2007) also reported that low concentrations of GeO 2 (up to 0.5 mg L -1 ) might sometimes have a slightly positive effect on growth of brown algae. After 5 days, F v /F m and rETR max significantly decreased in Ge-treated embryos, relative to control.…”
Section: Photosynthetic Responsesmentioning
confidence: 96%
“…In addition, the omission of Si from the growth media for brown algae has no apparent deleterious effects (McLachlan 1977). Thus the physiological basis for Ge toxicity in brown algae is unlikely to be similar to that in diatoms, and Shea and Chopin (2007) even reported positive growth responses of low concentrations of GeO 2 on S. latissima (L.) Lane et al (as Laminaria). More recently Mizuta and Yasui (2011) showed extensive silicon localization in sporophyte tissue of S. japonica (Areschoug) Lane et al There have been several studies on the direct effects of Ge on algal growth and morphology (McLachlan 1977, Yang 1993, Shea and Chopin 2007.…”
Section: Pulse Amplitude Modulated (Pam) Fluorometrymentioning
confidence: 99%
See 1 more Smart Citation